Application of photogrammetry for spatial free surface elevation and velocity measurement in wave flumes. (August 2019) - Fleming, Alan; Winship, Brian; Macfarlane, Gregor
This article presents a method for obtaining the spatial free surface elevation and velocity field for the water surface in a wave flume over a relatively large measurement area for this type of application (approximately 1.5 m × 1.5 m). The technique employs proprietary videogrammetry software to post-process stereo images captured by multiple synchronised machine vision cameras. Dimensional resolution and other limitations are similar to that experienced for particle imaging velocimetry systems ( x, y resolution of 2 mm). Imaging of the free surface was enabled by the use of millions of bespoke slightly positively buoyant fluorescent flakes. Ultraviolet light was used as the primary light source to excite the fluorescent flakes. Reflected ultraviolet light was attenuated by a high-pass filter fitted to the cameras so that only the emitted light from the fluorescent flakes was visible. The software was validated using a simple linear translation experiment. An application is demonstrated for the radiated wave field generated from a submerged sinusoidal heaving sphere for two cases: one single and five consecutive oscillations. Results agree with linear wave theory which indicates that the floating flakes had minimal impact on the water surface particle motion at the scale tested. It is, therefore, concluded that spatial measurement of the free surface elevation and velocity using the method presented has good resolution over a large measurement field. The flakes were found to follow the free surface well, but the measurement area is constrained to where the pattern of flakes exists in the image. Hence, application of floating markers is not suitable for experiments with significant outflow/upwelling which would wash away the floating markers from the intended measurement area.